2021
DOI: 10.1155/2021/7529164
|View full text |Cite
|
Sign up to set email alerts
|

Pinin Induces Epithelial-to-Mesenchymal Transition in Hepatocellular Carcinoma by Regulating m6A Modification

Abstract: Pinin is a moonlighting protein localized in desmosomes and nucleus. It could promote the growth of hepatocellular carcinoma. Whether this protein can induce epithelial-to-mesenchymal transition (EMT) and malignant progression in HCC is unknown. This work found that Pinin prompts EMT in vitro and in vivo. Further mechanism study found that Pinin increases the level of N6-methyladenosine (m6A) modification of RNA by interacting with METTL3, which in turn induces snail1 expression. These findings suggest that Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“… 77 Qiao et al. 273 reported pinin, a protein localizes to desmosomes and nucleus, formed condensates with METTL3 then suppressed by 1,6‐hexanediol. Moreover, 1,6‐hexanediol prevents phase separation of SARS2‐NP, IDR‐rich scaffold protein NSP5, RNA chaperone NSP2, BRD4, and MED1 effectively.…”
Section: Regulatory Targets and Methods Of Biomolecular Condensatesmentioning
confidence: 99%
See 1 more Smart Citation
“… 77 Qiao et al. 273 reported pinin, a protein localizes to desmosomes and nucleus, formed condensates with METTL3 then suppressed by 1,6‐hexanediol. Moreover, 1,6‐hexanediol prevents phase separation of SARS2‐NP, IDR‐rich scaffold protein NSP5, RNA chaperone NSP2, BRD4, and MED1 effectively.…”
Section: Regulatory Targets and Methods Of Biomolecular Condensatesmentioning
confidence: 99%
“…1,6‐Hexanediol inhibits phase separation of architectural long noncoding RNA NEAT1 and prevents assembly process of paraspeckles 77 . Qiao et al 273 . reported pinin, a protein localizes to desmosomes and nucleus, formed condensates with METTL3 then suppressed by 1,6‐hexanediol.…”
Section: Regulatory Targets and Methods Of Biomolecular Condensatesmentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) refers to how epithelial cells are depolarized and transformed into mesenchymal cells due to certain factors ( Jiang et al, 2022 ). During the metastasis in epithelial tumors, the phenotype of tumor cells changes primarily caused by environmental stimuli that enable tumor cells to adapt to the various microenvironments they encounter (intercellular stroma, humoral components, or blood) ( Park et al, 2020 ; Qiao et al, 2021 ). EMT regulates these phenotypic transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes have been proposed as a therapeutic tool to control the development of EMT and influence the progression of cancer[ 10 ]. In addition, Pinin induces EMT and malignant progression in hepatocellular carcinoma[ 11 ]. Furthermore, Wu et al [ 12 ] found that interleukin (IL)-6 secreted by cancer-associated fibroblasts promotes EMT and GC metastasis through the JAK2/STAT3 signaling pathway, Li et al [ 13 ] reported that tumor-associated neutrophils induce EMT by IL-17a to promote migration and invasion in GC cells, and Tian et al [ 14 ] reported that SERPINH1 regulates EMT and GC metastasis through the Wnt/β-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 99%